Worship choices and wellbeing of Australian churchgoing Catholics during COVID-19 church closures - Martyr, Philippa J. (Mental health, religion & culture, 2022)
Catholic worship prioritises in-person ritual contact, but due to COVID-19, most Australian places of worship closed during 2020. An online survey of 1173 Australian churchgoing Catholics using the Spiritual Well Being Scale found no significant difference in Existential and Religious Wellbeing scores between groups who were still experiencing church closures and those who could attend church again. In those still experiencing church closures, standard multiple regression revealed significant and positive relationships between age and virtual worship engagement and both Existential and Religious Wellbeing scores. However, in those who could attend church once more, pre- and post-closure Mass attendance rate, and both virtual and real-life worship during church closures were all predictive of higher Existential and Religious Wellbeing scores. These results support the provision of access to both virtual and real-life worship during church closures, and their positive effects on both existential and religious wellbeing in a churchgoing Catholic population.